Three-Component Covalent Organic Framework Nanosheets for the Detection of MicroRNAs - Bin Xie; Yilun Yan; Jialin Wu; Xinting Cai; Jiayue Zheng; Yixin Lan; Xihao Tang; Jun Fan; Shengrun Zheng; Songliang Cai (Crystals, 2022)
The development of new techniques for the detection of microRNAs (miRNAs) is highly desirable. Herein, a new crystalline three-component covalent organic framework (COF) termed EB-TAPB-TFP COF was synthesized under solvothermal conditions utilizing 1,3,5-triformylphloroglucinol, 1,3,5-tris(4-aminophenyl)benzene and ethidium bromide as monomers. Interestingly, EB-TAPB-TFP COF can be self-exfoliated into two-dimensional nanosheets (NSs) in an aqueous medium. The obtained EB-TAPB-TFP NSs exhibited a remarkable fluorescence intensity enhancement in the presence of a DNA-miRNA heteroduplex when compared to the presence of single-stranded DNA and other phosphate-based small molecules, making it promising in the detection of miRNA without tagging any fluorescent marker. Moreover, the EB-TAPB-TFP NSs can also be used as sensing material for the detection of a DNA-miRNA heteroduplex using the quartz crystal microbalance technique, which is in good agreement with the fluorescence sensing result. The exploration of COF-based sensors in this work demonstrates a new pathway for the selective detection of miRNAs.